Monetary policy and the role of inventory investment - Rubio, Margarita; Schuh, Scott (Taylor and Francis, 2017)
In this paper, we develop a dynamic stochastic general equilibrium model (DSGE) with sticky prices and inventory investment to explore the relationship between inventories and monetary policy. We use the traditional inventory literature as a basis to motivate this extension of the benchmark model and propose inventories as a factor of production. Within this setting, we test the empirical results in Irvine and Schuh (2005), who find that, since the mid-80s, monetary policy changed its target towards the inventory component of GDP. We explore this idea in our theoretical model and conclude through simulations that this is a plausible complementary explanation for the reduction in output volatility that was observed during the Great Moderation period.